(x-c-b)/a+(x-a-c)/b+(x-a-b)/c=3,1/a+1/b+1/c不等于零,求x-a-b-c
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 04:20:58
(x-c-b)/a+(x-a-c)/b+(x-a-b)/c=3,1/a+1/b+1/c不等于零,求x-a-b-c(x-c-b)/a+(x-a-c)/b+(x-a-b)/c=3,1/a+1/b+1/c不
(x-c-b)/a+(x-a-c)/b+(x-a-b)/c=3,1/a+1/b+1/c不等于零,求x-a-b-c
(x-c-b)/a+(x-a-c)/b+(x-a-b)/c=3,1/a+1/b+1/c不等于零,求x-a-b-c
(x-c-b)/a+(x-a-c)/b+(x-a-b)/c=3,1/a+1/b+1/c不等于零,求x-a-b-c
(x-c-b)/a+(x-a-c)/b+(x-a-b)/c-3=0
把-3拆成-1-1-1
[(x-c-b)/a-1]+[(x-a-c)/b-1]+[(x-a-b)/c-1]=0
(x-a-c-b)/a+(x-a-c-b)/b+(x-a-c-b)/c=0
(x-a-c-b)(1/a+1/b+1/c)=0
1/a+1/b+1/c不等于零
所以x-a-b-c=0
化简 :a+x/(a-b)(a-c) + b+x/(b-a)(b-c) + c+x/(c-a)(c-b)
(x-b)(x-3)(b-c)+(x-c)(x-a)(c-a)+(x-a)(x-b)(a-b)怎么解,
因式分解 x^2+(a+b+c)x+(a+b)c
因式分解x^2+(a+b+c)x+(a+b)c
因式分解:x(a-b)(b-c)(c-a)-y(b-a)(c-b)(a-c)
已知:x=a/b+c=b/a+c=c/a+b求x
(a-b-c)X( b+c-a)^2X(c-a+b)^3=?
(x-c-b)/a+(x-a-c)/b+(x-a-b)/c=3,1/a+1/b+1/c不等于零,求x-a-b-c
解关于x的方程a/x+a+b/x+b+c/x+c=3,a/x+a+b/x+b+c/x+c不等于0
解关于x的方程a/(x+a)+b/(x+b)+c/(x+c)=3,a/x+a+b/x+b+c/x+c不等于0
(b-c)x平方+(c-a)x+(a-b)=0(b不等于c
解方程:(b-c)x^2+(c-a)x+(a-b)=0(b≠c)
f(x)=(x-a)(x-b)(x-c),则a/f^(a)+b/f^(b)+c/f^(c)=?
解关于x的方程x+a+b/c+x+b+c/a+x+c+a/b=-3
已知函数f(x)=(x-a)(x-b)+(x-b)(x-c)+(x-c)(x-a),其中,a
x=(a+b)/c=(b+c)/a=(c+a)/b
若a,b,c满足不等式b+c>a,且(a-b-c)x
x(a-b)分之c,y(b-c)分之a,z(c-a)分之b 通分